Pengaruh E-Commerce Shopee dan Pendapatan Terhadap Perilaku Konsumtif Masyarakat Desa Pulau Rajak Kecamatan Betung Perspektif Ekonomi Syariah - Wiwik Wiwik; Zuul Fitriani Umari; Oki Sania Riski (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Consumptive behavior is a situation where a person has a desire to consume products that are actually not needed excessively in order to achieve satisfaction alone. With income and ease of using e-commerce, it can cause changes in people's consumption behavior. This is because people feel that shopee e-commerce is the most accessible online shopping platform . In addition, whatever item they are looking for is always there with many options and at a cheaper price. Therefore, people prefer to shop online through shopee e-commerce, both to meet their needs and only for items that are not really needed. This study aims to determine the influence of shopee e-commerce and income on consumptive behavior. The method used in this study is quantitative with multiple linear regression analysis methods. The results of this study are that shopee e-commerce (X1) has a significant influence on consumptive behavior (Y) as seen from the results of the t-test it is known that the value of sig is 0.002 <0.05 and revenue (X2) has a significant influence on consumptive behavior (Y) seen from the t-test it is known that the value of sig is 0.005 < 0.05. It can be concluded that shopee e-commerce and income have an effect on the consumptive behavior of the people of Rajak Island Village, Betung District from the perspective of sharia economics.